Environmental effects on the circadian systems of a diurnal ( rhabdomys dilectus) and noctural (micaelamys namaquensis) rodent species with specific reference to light pollution - Oosthuizen, Marietjie (University of Pretoria, 2020)
Dissertation (MSc)--University of Pretoria, 2019.